The unknown ajax ebook - Heyer, Georgette (Regency Romances, 2011)
The Queen of Regency Romance, bestselling author Georgette Heyer, brings her trademark charm and wit to this pitch-perfect comedic romp. A past dispute . . . When the irascible Lord Darracott's eldest son dies unexpectedly, the noble family must accept their estranged Yorkshire cousin as heir apparent. They are convinced he will prove to be a sadly vulgar person, but nothing could have prepared the beleaguered family for the arrival of Major Hugo Darracott . . . A present deception . . . His clever and beautiful cousin Anthea is sure there's more to the gentle giant than Hugo's innocent blue eyes and broad Yorkshire brogue would lead one to believe. But even she doesn't guess what he's capable of, until a family crisis arises and only Hugo can preserve the family's honor, leading everybody on a merry chase in the process . . . Praise for The Unknown Ajax: "Wonderful entertainment from first page to last."—Chicago Sunday Tribune